2010
DOI: 10.1097/acm.0b013e3181eac1e0
|View full text |Cite
|
Sign up to set email alerts
|

Taking Note of the Perceived Value and Impact of Medical Student Chart Documentation on Education and Patient Care

Abstract: Although students' ability to enter notes in patients' records is believed to be important for student education, only about half of all hospitals allow all students' notes in the EMR. Policies regarding placement of student notes should be implemented to ensure students' competency in note writing and their value as members of the patient care team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 4 publications
2
43
0
Order By: Relevance
“…Our study found that the most common reason students were not allowed to document in the EHR was due to hospital/medical school institutional policies. Given that 90% of medical school deans felt students should document in the chart and 93% felt that student education would be adversely affected if this were not allowed,7 there appears to be a disconnect between educational goals and institutional policies related to documentation. It is possible that some of these policies could be due to concerns over medical liability, which emerged as another major reason for non-use even if not explicitly prohibited by hospital policy.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the most common reason students were not allowed to document in the EHR was due to hospital/medical school institutional policies. Given that 90% of medical school deans felt students should document in the chart and 93% felt that student education would be adversely affected if this were not allowed,7 there appears to be a disconnect between educational goals and institutional policies related to documentation. It is possible that some of these policies could be due to concerns over medical liability, which emerged as another major reason for non-use even if not explicitly prohibited by hospital policy.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys regarding student use of EHR 7,8 show broad institutional variation. Most differences are the result of varying local interpretations of Medicare guidelines on student EHR use.…”
Section: Electronic Health Records: How Will Students Learn If They Cmentioning
confidence: 99%
“…15,16 In fact, a review of articles published in Academic Medicine from 2010 to 2012 revealed 9 national survey studies on medical schools in which the response rates were as low as 51% to 64%. [17][18][19][20][21][22][23][24][25] …”
Section: Is Response Rate a Standard For Publication?mentioning
confidence: 99%